2019
DOI: 10.1002/cbic.201900040
|View full text |Cite
|
Sign up to set email alerts
|

Mannopyranoside Glycolipids Inhibit Mycobacterial and Biofilm Growth and Potentiate Isoniazid Inhibition Activities in M. smegmatis

Abstract: Lipomannan and lipoarabinomannan are integral components of the mycobacterial cell wall. Earlier studies demonstrated that synthetic arabinan and arabinomannan glycolipids acted as inhibitors of mycobacterial growth, in addition to exhibiting inhibitory activities of mycobacterial biofilm. Herein, it is demonstrated that synthetic mannan glycolipids are better inhibitors of mycobacterial growth, whereas lipoarabinomannan has a higher inhibition efficiency to biofilm. Syntheses of mannan glycolipids with a grad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…smegmatis biofilm and potentiate isoniazid killing (Figure ). Similar studies with synthetic glycolipids and arabinofuranosides were found to interfere with biofilm formation and maturation in M . smegmatis (Figure ).…”
Section: Biofilm Inhibitionmentioning
confidence: 99%
See 1 more Smart Citation
“…smegmatis biofilm and potentiate isoniazid killing (Figure ). Similar studies with synthetic glycolipids and arabinofuranosides were found to interfere with biofilm formation and maturation in M . smegmatis (Figure ).…”
Section: Biofilm Inhibitionmentioning
confidence: 99%
“…Arabinomannan-containing glycolipids have been shown to possess potent antibiofilm activity against M. smegmatis biofilm and potentiate isoniazid killing (Figure 7). 18 Similar studies with synthetic glycolipids and arabinofuranosides were found to interfere with biofilm formation and maturation in M. smegmatis (Figure 7). 19 The synthetic compound 4-hydroxy-2-pyridone is effective against M. smegmatis in biofilm formation.…”
Section: ■ Biofilm Inhibitionmentioning
confidence: 99%